Enhancing Teacher Performance In Digital Era: A Study On Transfomational Leadership, Creativity, And Motivation: - Indrawati, Nina; Hidayat, Nandang; Hendarman (UNIVERSITAS PAKUAN, 2025)
This study analyzed the influence of transformational leadership, teacher creativity, and work motivation on teacher performance in the digital age, motivated by challenges in adapting to technological development and the Merdeka Curriculum policy. The study used a quantitative approach with survey methods and statistical analysis, including path analysis. The sample comprised 254 permanent foundation teachers at private junior high schools in Bogor City. Results showed positive direct influences between: Transformational leadership on teacher performance (βy1 = 0.385). Teacher creativity on teacher performance (βy2 = 0.305). Work motivation on teacher performance (βy3 = 0.341).Transformational leadership on work motivation (β31 = 0.257). Teacher creativity on work motivation (β32 = 0.203). Transformational leadership showed indirect influence on teacher performance through work motivation (βy31 = 0.098). Teacher creativity on teacher performance through work motivation (βy32 = 0.061). The study concluded that transformational leadership, teacher creativity, and work motivation significantly influence teacher performance, with work motivation mediating the effects of leadership and creativity. These findings inform strategies to enhance teacher performance through leadership, pedagogical creativity, and motivation.